Snake Deltavirus Utilizes Envelope Proteins of Different Viruses To Generate Infectious Particles - Leonora Szirovicza (American Society for Microbiology, 2020)
ABSTRACT Satellite viruses, most commonly found in plants, rely on helper viruses to complete their replication cycle. The only known example of a human satellite virus is the hepatitis D virus (HDV), and it is generally thought to require hepatitis B virus (HBV) to form infectious particles. Until 2018, HDV was the sole representative of the genus Deltavirus and was thought to have evolved in humans, the only known HDV host. The subsequent identification of HDV-like agents in birds, snakes, fish, amphibians, and invertebrates indicated that the evolutionary history of deltaviruses is likely much longer than previously hypothesized. Interestingly, none of the HDV-like agents were found in coinfection with an HBV-like agent, suggesting that these viruses use different helper virus(es). Here we show, using snake deltavirus (SDeV), that HBV and hepadnaviruses represent only one example of helper viruses for deltaviruses. We cloned the SDeV genome into a mammalian expression plasmid, and by transfection could initiate SDeV replication in cultured snake and mammalian cell lines. By superinfecting persistently SDeV-infected cells with reptarenaviruses and hartmaniviruses, or by transfecting their surface proteins, we could induce production of infectious SDeV particles. Our findings indicate that deltaviruses can likely use a multitude of helper viruses or even viral glycoproteins to form infectious particles. This suggests that persistent infections, such as those caused by arenaviruses and orthohantaviruses used in this study, and recurrent infections would be beneficial for the spread of deltaviruses. It seems plausible that further human or animal disease associations with deltavirus infections will be identified in the future. IMPORTANCE Deltaviruses need a coinfecting enveloped virus to produce infectious particles necessary for transmission to a new host. Hepatitis D virus (HDV), the only known deltavirus until 2018, has been found only in humans, and its coinfection with hepatitis B virus (HBV) is linked with fulminant hepatitis. The recent discovery of deltaviruses without a coinfecting HBV-like agent in several different taxa suggested that deltaviruses could employ coinfection by other enveloped viruses to complete their life cycle. In this report, we show that snake deltavirus (SDeV) efficiently utilizes coinfecting reptarena- and hartmaniviruses to form infectious particles. Furthermore, we demonstrate that cells expressing the envelope proteins of arenaviruses and orthohantaviruses produce infectious SDeV particles. As the envelope proteins are responsible for binding and infecting new host cells, our findings indicate that deltaviruses are likely not restricted in their tissue tropism, implying that they could be linked to animal or human diseases other than hepatitis.